RISK FACTORS OF BREAST CANCER IN WOMEN IN MONTENEGRO - Brajkovic, Jelena; Pelicic, Damir; Saveljic, Mitar (HEALTH CARE, 2023)
Introduction/Aim: Numerous risk factors are associated with breast cancer, which is the leading cause of morbidity and mortality in the world. The aim of this study was to analyze the factors that lead to the occurrence of breast cancer. Methods: This case study included 154 women who were diagnosed with breast cancer for the first time during 2018 at the Clinical Center for Oncology and Radiotherapy of Montenegro. Data were collected from all respondents using a questionnaire. Results: The average age of women with breast cancer was 46.42 (±12.77). The reproductive characteristics of women show that 95.5% of women had menarche before the age of 15, while 85.7% of them had child/children. The largest number of women (86.4%) gave birth to a child between the ages of 26 and 32. Of all the women who gave birth to a child, 31.8% had one child, 49.3% two children and 18.9% three and more children. The majority of women (86.4%) were breastfeeding their children. About 1/3 of respondents used the oral contraception regularly. Every second woman was a current smoker, and 28.6% were ex-smokers. Alcohol was regularly consumed by 3.9% of women, and occasionally by 81.2%. 63.6% of women had a healthy diet, while 85.1% were physically active on a daily basis. 16.2% of women had a positive family history of breast cancer. As far as preventive activities are concerned, women with breast cancer in 92.9% cases had breast examinations by gynecologists, 36.4% knew the technique of self-examination, while 33.8% of respondents (that is, 58.4% of women aged 50 years and older) underwent mammography. Conclusion: It is necessary to choose healthy lifestyles and educate oneself about the importance of preventive breast examinations, learn the techniques of self-examination of breasts and realize the importance of mammography as a screening test for the early detection of breast cancer, which is recommended between the ages of 50 and 69, every two years. Thus, treatment costs are drastically reduced, better outcomes are ensured, and first of all, the quality of life is improved.